2006
DOI: 10.1002/anie.200600512
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Counteranion‐Directed Catalysis

Abstract: Exceedingly high enantioselectivity in a catalytic reaction can be realized even when the chirality resides only in the counteranion of the catalyst. A salt (1) composed of an achiral ammonium cation and a chiral phosphate counteranion catalyzes asymmetric transfer hydrogenations of aromatic and aliphatic α,β‐unsaturated aldehydes with a Hantzsch ester in excellent enantioselectivities (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
180
0
16

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 544 publications
(197 citation statements)
references
References 31 publications
1
180
0
16
Order By: Relevance
“…Zunächst führt die reversible Addition der primären Alkoholfunktion des Diols an den Aldehyd zur Bildung eins Halbacetal-Intermediats A. Protonierung seiner OH-Funktion durch den Katalysator führt zur Eliminierung von Wasser und der Entstehung des entscheidenden Oxocarbeniumionen-Intermediats B. Das chirale Imidodiphosphat-Gegenanion sorgt für eine chirale Umgebung des Oxocarbeniumkations [13] und wirkt als Base, die den nucleophilen Angriff der zweiten Alkoholgruppe auf die si-Seite des Oxocarbeniumions dirigiert, wodurch das Skonfigurierte cyclische Acetal entsteht.…”
Section: Angewandte Zuschriftenunclassified
“…Zunächst führt die reversible Addition der primären Alkoholfunktion des Diols an den Aldehyd zur Bildung eins Halbacetal-Intermediats A. Protonierung seiner OH-Funktion durch den Katalysator führt zur Eliminierung von Wasser und der Entstehung des entscheidenden Oxocarbeniumionen-Intermediats B. Das chirale Imidodiphosphat-Gegenanion sorgt für eine chirale Umgebung des Oxocarbeniumkations [13] und wirkt als Base, die den nucleophilen Angriff der zweiten Alkoholgruppe auf die si-Seite des Oxocarbeniumions dirigiert, wodurch das Skonfigurierte cyclische Acetal entsteht.…”
Section: Angewandte Zuschriftenunclassified
“…[23,24] In addition, their corresponding bases should be useful in applications of asymmetric counteranion-directed catalysis (ACDC). [25][26][27] Recently, a highly acidic binaphthyl-derived chiral disulfonic acid catalyst has been designed and synthesized. [28][29][30] The corresponding chiral cyclic disulfonimides have been unknown but appeared to us as a particularly promising chiral catalyst motif.…”
mentioning
confidence: 99%
“…Prior to testing the enantiocontrol with catalytic systems based on the resolved bicycles we explored the possibility for counter ion directed organocatalysis. 5,30,31 Control experiments confirmed that rac-5a, in combination with either (þ)-or (À)-CSA, furnished products with essentially with no enantioenrichment. Similarly, no enhancement was observed with (þ)-or (À)-1,1 0 -binaphthyl-2,2 0 -diyl hydrogen phosphate 9 nor with the more sterically demanding (R)-TRIP 13 as co-catalyst with rac-5a; in the case of (R)-TRIP, limited solubility of the co-catalyst is reflected in the poor chemical yield, results are summarised in Table 4, entries 1e5.…”
Section: Resultsmentioning
confidence: 87%
“…1e3 A range of catalyst architectures with varying modes of operation have been developed and whilst SOMO 4 and counter ion catalysis 5 are at early stages of development many applications of enamine, 6 iminium 7 and hydrogen bonding catalysis 8 have been reported. To-date the most successful catalysts are derivatives of the five-membered, secondary amine heterocycles proline 9 and imidazolidinone.…”
Section: Introductionmentioning
confidence: 99%